Harmonisation of shari‘ah and law: approaches and progress - Mohd Zin, Najibah (Harun M Hashim Law Centre, IIUM, 2023)
This book is a collection of articles enlisting the expertise and experiences of lecturers from Ahmad Ibrahim Kulliyyah of Laws from various legal disciplines by using harmonisation of laws as the central theme. In accommodating diverse approaches of the law, the book is divided into several parts, namely methodology of harmonisation; family, land and property law; criminal law and evidence; and health and Islamic legal system. The novelty of this book is that it speaks to a wide range of themes with one voice that tries to link the legal theory to practice by using harmonisation of laws as the methodological tools in searching for the best approach principles. This is practically relevant in a legal system with dual jurisdictions such as Malaysia, where conflict of law is bound to happen. Thus, conceptualizing comparative analysis, expounding the concept of wasatiyyah as a balanced approach and selecting preferred approach principles are among the methodological tools that could be useful in achieving peace, just and balanced law. The literatures on family, land and property matters focus on localized legal issues by analysing conflicting civil and Shari‘ah laws and exploring their compatibility in reconciling the conflicts. The discussion is geared towards conceptualizing Shari‘ah law as dynamic and the preferred option as a practical legal solution. Apart from looking into Shari‘ah as the main focus, the literatures explore the possibility of benchmarking with other Western legal systems in the aspect of procedural law in searching for a better solution to the legal proceedings. This study is useful in widening the scope of harmonisation of laws so as not to confine to civil and Shari‘ah law solely but accepting any legal solutions in promoting just and balanced law which is the cornerstone in any legal system, including Shari‘ah law.